Building Independent Generations from an Early Age: The Crucial Role of Early Childhood Education Teachers - Nurwita, Syisva; Syaputra, Abdul Yongky (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to find out the crucial role of early childhood education teachers in fostering children’s independence from an early age. This research was conducted using a qualitative descriptive method with data collection through observation, interviews, and documentation. The main subjects in this study were teachers and children. The results of the study show that the role of teachers in increasing children’s independence by providing opportunities for children, and applying learning in school. The role of a supervisor is carried out in a way that teachers habituate and repeat to children, teachers who have extensive knowledge, and teachers who instill a neat attitude in children. Independent children always want to try their own way in doing things, not depend on others and children know when the time to ask others for help. This study contributes that the special methods used by teachers to instill independent character values in children are using habituation methods, storytelling methods, affirmation methods, singing, poetry, and knowing, feeling, and direct practice both at school and at home so that the application of independent character values is more imprinted in children.